Diversity analysis of the endosymbiotic bacterial community in field-collected Haemaphysalis ticks on the tropical Hainan Island, China - Lu, Yajun; Yang, Siqi; Zhao, Qiuyu; Yuan, Chuanfei; Xia, Qianfeng (Folia parasitologica, 2023)
Ticks are important vectors of various pathogens that cause infectious diseases in humans. Endosymbiotic bacteria have been explored as targets for tick and tick-borne disease control. However, the tick bacterial community on Hainan Island, which is the largest tropical island in China and has an environment favourable to ticks, has not yet been studied. In this study, we surveyed the bacterial community of ticks collected from grass in one village in Haikou. A total of 20 ticks were morphologically and molecularly identified as Haemaphysalis spp. The tick bacterial 16S rRNA hypervariable region amplicon libraries were sequenced on an Illumina MiSeq platform. A total of 10 possible bacterial genera were detected, indicating a low-diversity bacterial community profile. The dominant bacterial genus, Massilia, accounted for 97.85% of the population. Some other bacterial genera, including Arsenophonus and Pseudomonas, have been reported to play a role in tick development and tick-borne pathogen transmission in other tick species. Overall, the study highlights the first descriptive understanding of the tick bacterial community on Hainan Island and provides a basis for deciphering the interactions between the tick microbiome and tick-borne pathogens.
Keywords: tropics; Animals; RNA, Ribosomal, 16S; China; 16S rRNA; lidé; klíšťata; endosymbiotic bacteria; zvířata; Ticks; Illumina MiSeq; Bacteria; bacterial community; RNA ribozomální 16S; Ixodidae; Čína; Humans